2010
DOI: 10.1016/j.meatsci.2009.12.014
|View full text |Cite
|
Sign up to set email alerts
|

High pressure induced changes on sarcoplasmic protein fraction and quality indicators

Abstract: The combined effect of pressure and mild temperature treatments on bovine sarcoplasmic proteins and quality parameters was assessed. M. longissimus dorsi samples were pressurised in a range of 200-600 MPa and 10-30 degrees C. High Pressure Processing (HPP) induced a reduction of protein solubility (p<0.001) compared to non-treated controls (NT), more pronounced above 200 MPa. HPP at pressures higher than 200 MPa induced a strong modification (p<0.001) of meat colour and a reduction of water holding capacity (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
116
1
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(138 citation statements)
references
References 33 publications
12
116
1
7
Order By: Relevance
“…Changes in sarcoplasmic proteins, which play an important role in the binding properties of water in raw meat (Joo et al 1999), might also be related to decreased cooking loss during high-pressure processes. In the same way, Marcos et al (2010) observed a negative correlation between the solubility of the sarcoplasmic protein and moisture in bovine muscle (Longissimus dorsi) suggesting that the denaturation of sarcoplasmic proteins induced by pressure can have a negative effect on water binding in pressurized meats.…”
Section: Introductionmentioning
confidence: 75%
“…Changes in sarcoplasmic proteins, which play an important role in the binding properties of water in raw meat (Joo et al 1999), might also be related to decreased cooking loss during high-pressure processes. In the same way, Marcos et al (2010) observed a negative correlation between the solubility of the sarcoplasmic protein and moisture in bovine muscle (Longissimus dorsi) suggesting that the denaturation of sarcoplasmic proteins induced by pressure can have a negative effect on water binding in pressurized meats.…”
Section: Introductionmentioning
confidence: 75%
“…2a. An increase in L* values is the most often reported modifications occurring in raw meat at above the pressure levels of 200 MPa (Del Olmo et al 2010;Marcos et al 2010). The changes in lightness are due to the myofibrillar proteins denaturation (Goutefongea et al 1995) and also myoglobin denaturation (Carlez et al 1993).…”
Section: Effect Of High Pressure On Color Characteristics Of Raw Chevmentioning
confidence: 99%
“…The proteins in meat (sarcoplasmic and myofi brillar) change during the high pressure treatment (MARCOS et al, 2010), due to aggregation and denaturation (GALAZKA et al, 2000;IWASAKI et al, 2006). At the same time, the changes in proteins depend on some environmental conditions, which are not fully understood yet (BUCKOW et al, 2013).…”
Section: Effects Of High Pressures On Protein Profi Lementioning
confidence: 99%